PENGARUH KUALITAS LAYANAN, BIAYA PENDIDIKAN DAN FASILITAS PENDIDIKAN TERHADAP KEPUTUSAN KONSUMEN DENGAN BRAND IMAGE SEBAGAI VARIABEL INTERVENING DALAM MEMILIH PROGRAM STUDI PADA FAKULTAS EKONOMI UNIVERSITAS KRISTEN ARTHA WACANA KUPANG - RANE, MELVIN K DJAMI; RIDWAN, M SIHAB; WARDAH, WARDAH (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2019)
ABSTRACTHigher education is one of the most important priorities for most people. For some people, education can go to Higher Education is the hope to be achieved. Deciding to continue education to Higher Education, the community will be faced with a variety of factors underlying their decision. This study aims to determine whether the factors of Service Quality, Education Costs and Educational Facilities Against Consumer Decisions with Brand Image as Intervening Variables in Choosing a Study Program at the Faculty of Economics, Artha Wacana Christian University Kupang. The data of this study were collected from 1100 students at the Artha Wacana Kupang University of Economics Faculty of Kupang who were respondents in this study and the technique used was random sampling method. The test result data processed using Structural Equation Modeling (SEM) contained the following results: The independent variables that most influence on the dependent variable is the variable of Brand Image on Consumer Decision (0326), followed by a variable Quality of Service on Brand Image (0302), followed by the Service Quality variable on Consumer Decisions (0.273), followed by the Education Cost variable on Brand Image (0.254), followed by the Education Facility variable towards Brand Image (0.214), followed by the Education Cost variable on Consumer Decisions (0.167), followed by the Education Facility variable on Consumer Decisions (0.032). The results prove that the independent variables (service quality, education costs, and educational facilities) influence the intervening variables, namely Brand image and the dependent variable, namely consumer decisions in Selecting the Study Program at the Faculty of Economics, Artha Wacana Christian University, Kupang.Â Keywords: Structural Equation Modeling (SEM), Service Quality, Education Costs, Educational Facilities, Brand Image, Consumer Decisions.